Immunofluorescence and its application in dermatopathology with oral manifestations: Revisited - R S Arvind Babu; P Chandrasekar; K Lalith Prakash Chandra; G Sridhar Reddy; K Krian Kumar; B V Ramana Reddy (Wolters Kluwer Medknow Publications, 2013)
The use of fluorescence probes the field of cell and molecular biology. Immunofluorescence is a molecular method for detection of antigen or antibody in a tissue section/serum sample. Although histopathology remains gold standard for most of auto immune, immune mediated and vesiculo - bullous diseases. Immunofluorescence is an ancillary investigation, which are used to support clinical diagnosis more evidently. This method provides additional diagnostic, prognostic information and remains more specific diagnostic aid for vesiculo - bullous diseases of skin. This review article discusses about immunofluorescence techniques and its application in dermatopathology with oral manifestations.